Die impak van die verbond op 'n paradigma vir pastoraat - J. Janse van Rensburg; L. Hoffman (Acta Theologica)
This article points out that the covenant has a more comprehensive impact on pastoral care than other paradigms. It is indicated that the contents communicated to the believer as well as the techniques used are influenced by a covenantal paradigm for pastoral care. From a covenantal perspective, a believer can be equipped to regard his/her life within the framework of the covenant. The actions and experiences of the believer are influenced by this sentence: “I will establish my covenant between me and you and your descendants after you … to be your God and the God of your descendants” (Gen. 17:7)